The provisional application of international treaties - Sturma, P. (Право и государство, 2013)
The present article deals with a provisional application of international treaties. This issue has important implications both in international law and in constitutional law of the states. The main point of the article is that there is not a provisional entry into force of the international treaties but a provisional application of certain provisions of the international treaties prior to its entry into force. The provisional application of the international treaties implies a lot of problems in practice and that’s why this issue is under work of the UN International Law Commission.
Keywords: codification; international treaties; provisional application; International Law Commission; Vienna Convention on the Law of Treaties; Research Subject Categories::LAW/JURISPRUDENCE